How Do Red Blood Cells Die? - Thiagarajan, Perumal; Parker, Charles J.; Prchal, Josef T. (Frontiers in Physiology, 2021)
Normal human red blood cells have an average life span of about 120 days in the circulation after which they are engulfed by macrophages. This is an extremely efficient process as macrophages phagocytose about 5 million erythrocytes every second without any significant release of hemoglobin in the circulation. Despite large number of investigations, the precise molecular mechanism by which macrophages recognize senescent red blood cells for clearance remains elusive. Red cells undergo several physicochemical changes as they age in the circulation. Several of these changes have been proposed as a recognition tag for macrophages. Most prevalent hypotheses for red cell clearance mechanism(s) are expression of neoantigens on red cell surface, exposure phosphatidylserine and decreased deformability. While there is some correlation between these changes with aging their causal role for red cell clearance has not been established. Despite plethora of investigations, we still have incomplete understanding of the molecular details of red cell clearance. In this review, we have reviewed the recent data on clearance of senescent red cells. We anticipate recent progresses in in vivo red cell labelling and the explosion of modern proteomic techniques will, in near future, facilitate our understanding of red cell senescence and their destruction.